Pelatihan Las Tungsten Inert Gas (TIG) Bagi Siswa SMK - Djuanda Djuanda; Fiskia Rera Baharuddin; Baso Riadi Husda; Hamza Nur; Ismail Aqsa (V-MACHINE: Vocational and Mechanical Community Service Journal, 2024)
There are still many students at SMKN 5 Bulukumba who do not understand TIG (Tungsten Inert Gas) welding technology. Even as vocational school students, they have a high desire to get to know the latest technology, especially in the field of welding engineering. This is because at SMKN Bulukumba there is not much TIG welding equipment available, besides the cost of operating this equipment is higher compared to electric arc welding (SMAW). Therefore, with this service in the form of TIG welding technique training for students at SMKN 5 Bulukumba, South Sulawesi province, it is hoped that it can provide knowledge and skills in the field of welding techniques and can provide them with the opportunity to increase their competency in the field of welding. The location for community service is carried out at SMKN 5 Bulukumba, Bontoharu Village, Rilau Ale District, Bulukumba Regency. The aims of the service are: to help students and teachers gain knowledge and skills, especially in the field of TIG welding techniques, to help realize students' desires to improve their competence in the world of work to be able to compete with graduates from other vocational schools, and to be able to apply good TIG welding techniques.